Lectora Inspire Learning Media Based on Character Education in Civics - Fyra Aldira Audia; Linda Zakiah; Nidya Chandra Muji Utami (Universitas Pendidikan Ganesha, 2021)
In the era of revolution 4.0, technology has an essential role in education, but teachers do not use technology in learning so that the impact on the learning process is less than optimal. This study aims to develop Lectora inspire learning media based on character education in Civics learning. This type of research is development research. The research method uses the research and development (R&D) development model of Hannafin and Peck. Three experts validate the media. The product trial subjects were 15 students. Data collection techniques by filling out a questionnaire. Quantitative data analysis techniques are based on the results of the calculation of answers on a Likert scale. The validation results from material experts obtained a score of 87.5%. The results of the validation of media experts obtained a score of 85%. The results of the validation of linguists obtained a score of 81%. The teacher obtained a score of 98%. The results of product trials to students obtained a score of 98%. It can be concluded that the learning media Lectora inspire based on character education in Civics learning is feasible to be used as a learning medium. This research implies that this media can be used to build students' character.